Evaluation of Marine Algae Wakame (Undaria pinnatifida) and Kombu (Laminaria digitata japonica) as Food Supplements - Luciana Vallorani; Nada Milanović; Vilberto Stocchi; Nada Kolb (Food Technology and Biotechnology, 2004)
Crude proteins and their amino acid composition, -carotene, vitamins B1, B2, B6, niacin and minerals were determined in two edible brown marine algae (Phaeophyceae), Wakame (Undaria pinnatifida) and Kombu (Laminaria digitata japonica). The amino acid scores for five key essential amino acids, frequently deficient in mixed human diet, and essential amino acid index were calculated. The results have shown the presence of all essential amino acids. The values of essential amino acid ratios of analysed algae exceed the ratios of reference proteins suggested by FAO/WHO/UNU, except for tryptophan, the first limiting amino acid in both analysed algae. Iodine, the most important component of sea vegetables is present in high amounts as well as the vitamins B1, B2, B6, niacin and β-carotene. The content of minerals was found high, while the presence of heavy metals was negligible.